Propane σ‐Complexes on PdO(101): Spectroscopic Evidence of the Selective Coordination and Activation of Primary CH Bonds. Issue 47 (30th September 2015) - Zhang, Feng; Pan, Li; Choi, Juhee; Mehar, Vikram; Diulus, John T.; Asthagiri, Aravind; Weaver, Jason F.
Abstract: Achieving selective CH bond cleavage is critical for developing catalytic processes that transform small alkanes to value‐added products. The present study clarifies the molecular‐level origin for an exceptionally strong preference for propane to dissociate on the crystalline PdO(101) surface via primary CH bond cleavage. Using reflection absorption infrared spectroscopy (RAIRS) and density functional theory (DFT) calculations, we show that adsorbed propane σ‐complexes preferentially adopt geometries on PdO(101) in which only primary CH bonds datively interact with the surface Pd atoms at low propane coverages and are thus activated under typical catalytic reaction conditions. We show that a propane molecule achieves maximum stability on PdO(101) by adopting a bidentate geometry in which a HPd dative bond forms at each CH3 group. These results demonstrate that structural registry between the molecule and surface can strongly influence the selectivity of a metal oxide surface in activating alkane CH bonds. Abstract : The structural evolution of propane σ‐complexes on PdO(101) was investigated by using reflection absorption infrared spectroscopy and DFT calculations. Favorable dative bonding with the surface palladium atoms causes an exceptionally high selectivity for the activation of primary CH bonds.